George A. Romero's Land of the dead - Romero, George A.; Doherty, Michael; Universal Pictures (Firm).; Atmosphere Entertainment; Aurora Entertainment Corporation (Universal City, Calif. Universal; distributed in the Philippines by MagnaVision, 2005)
Zombies have become the dominant population, and they've begun to show signs of undead intelligence and gathering power. The wealthiest human survivors live comfortably in a luxury high-rise building that is barricaded within a safe zone. The wealthy ignore the horrors of the outside world while armed scavengers stage raids in the zombie- zone to gather much-needed food and supplies. Riley and Cholo are mercenaries-for-hire; Kaufman is their nefarious boss; and Slack is a former hooker recruited into Riley's scavenger squad.
Director of photography, Miroslaw Baszak ; art director, Douglas Slater ; editor, Michael Doherty ; music, Reinhold Heil, Johnny Klimek ; costume designer, Alex Kavanagh ; production designer, Arv Grewal ; visual effects supervisor, Jeff Campbell.
Simon Baker, John Leguizamo, Dennis Hopper, Asia Argento, Robert Joy.
MPAA rating: Unrated.
VCD.
Keywords: Zombies -- Drama; Mercenary troops -- Drama; Ragpickers -- Drama